Optimal first-line treatment for EGFR-mutated NSCLC: a comparative analysis of osimertinib and second-generation EGFR-TKIs - Hsu-Yuan Chen; Chia-Hung Chen; Wei-Chih Liao; Yu-Chao Lin; Hung-Jen Chen; Te-Chun Hsia; Wen-Chien Cheng; Chih-Yen Tu (BMC Pulmonary Medicine, 2024)
Abstract Background Osimertinib is an irreversible third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI). It is the preferred first-line treatment for EGFR-mutated non-small cell lung cancer (NSCLC) compared to first-generation EGFR-TKIs. However, limited research has compared its clinical effectiveness with second-generation (2nd G) EGFR-TKIs. Materials and methods This study recruited patients diagnosed with stage IIIb-IV EGFR-mutated NSCLC who received first-line treatment with either 2nd G EGFR-TKIs (afatinib and dacomitinib) or osimertinib between April 2020 and April 2023. Results The final analysis included 168 patients, of whom 113 received 2nd G EGFR-TKIs (afatinib or dacomitinib) and 55 received osimertinib. The median progression-free survival (PFS) did not differ significantly between 2nd G EGFR-TKIs and osimertinib (del 19: 17.6 months; L858R: 20.0 months vs. 28.3 months, p = 0.081). In patients with the EGFR exon 19 deletion, osimertinib conferred a longer median PFS (28.3 vs. 17.6 months, p = 0.118) and time to treatment failure (30.2 vs. 22.7 months, p = 0.722) than 2nd G EGFR-TKIs. However, the differences were not statistically significant. In patients with with the EGFR exon 19 deletion and central nervous system metastasis, the median PFS did not differ significantly between those treated with osimertinib (14.3 months) and those treated with 2nd G EGFR-TKIs (17.6 months; p = 0.881). Multivariate regression analysis revealed that the NSCLC stage was the only independent negative predictor of PFS. The treatment patterns in the second line also differed significantly between groups (p = 0.008). Conclusions This study found comparable effectiveness between osimertinib and 2nd G EGFR-TKIs as first-line treatment for advanced EGFR-mutated NSCLC, with only the NSCLC stage identified as a negative predictor of PFS. However, whether the different second-line treatments affect overall survival should be examined.